Antibiotic-resistant Campylobacter coli and Campylobacter jejuni in commercial and smallholder farm animals in the Asante Akim North Municipality of Ghana - Paintsil, Ellis Kobina; Ofori, Linda Aurelia; Akenten, Charity Wiafe; Zautner, Andreas E.; Mbwana, Joyce; Jaeger, Anna; Lamshöft, Maike; May, Jürgen; Obiri-Danso, Kwasi; Philipps, Richard Odame; Krumkamp, Ralf; Dekker, Denise (Frontiers in Microbiology, 2022)
Worldwide, farm animals, in particular poultry, are an important reservoir for Campylobacter spp. However, information on Campylobacter colonization in farm animals in Africa is scarce. Hence, this cross-sectional study determined antibiotic-resistant Campylobacter from both commercial and smallholder farm animals in the Asante Akim North Municipality of Ghana. Faecal samples from poultry and livestock kept by commercial and smallholder farms were collected and analysed using standard microbiological methods. The overall Campylobacter frequency was 20.3% (n/N = 322/1585), and frequencies detected were similarly high in isolates from commercial (21.0%, n/N = 169/805) and smallholder (19.6%, n/N = 153/780) farms. Species isolated were C. coli (67.7%, n/N = 218/322) and C. jejuni (32.3%, n/N = 104/322). However, the frequency of C. coli was 2.1 (95% CI: 1.8 – 2.5) times higher than what was found for C. jejuni. Campylobacter frequencies in the rainy season was 22.2% (n/N = 258/1160), and 15.1% (n/N = 64/425) in the dry season (prevalence ratio = 1.48, 95% CI: 1.2 – 1.9). About 1.7% (n/N = 6/322) of the Campylobacter isolates, all from smallholder farms, were susceptible to all antibiotics tested. Multidrug resistance was observed for 4.7% (n/N = 15/322) of the Campylobacter isolates, of which 93.3% (n/N = 14/15) occurred in isolates from commercial farms. This study highlights the need for the implementation of control programs, in commercial farming but also at the smallholder farm level, to formulate clear guidelines aimed at decreasing Campylobacter contamination of meat products and reducing the use of antibiotics in the farming sector.